Characterization of reference standards for dirt by Laser Ablation Induced Photoacoustics (LAIP) - Orzi, Daniel Jesús Omar (2010)
Measurements of surface cleanliness and dirt characterization are important problems in a wide range of processes in industry and production. Standard methods are in most cases cumbersome laboratory procedures that must be performed out of the production lines. Instruments and methods for cleanliness determination and dirt characterization require reference standards for calibration. For that purpose we built a possible dirt reference standard (DRS) made by films of graphite grease subjected to heat treatment for mechanical stabilization. The DRS characterization was performed by Laser Ablation Induced Photoacoustics (LAIP). The measurement of the thickness of the films was made by lowcoherence interferometry.